Education strategy in the developing world revising the World Bank's education policy - Collins, Christopher S.; Wiseman, Alexander W., 1968- (Bingley, U.K. : Emerald, 2012)
Following the development of a "Concept Note" for the World Bank Education Strategy 2020, the World Bank engaged in a series of activities to garner feedback about the new strategy. In early 2011, a revised strategy was published entitled, "Learning for All: Investing in People's Knowledge and Skills to Promote Development." The document ranges from explaining the role of education in development to the philosophy behind a new strategy and concludes with details about performance and impact indicators. To bring together the scholarly work and both evidence and expert opinion about the development practices of the Bank, this volume includes chapters/authors with a range of research interests, practical experience, and ideological backgrounds.
Education, development, and poverty : an introduction to research on the World Bank's education policy and revision process / Christopher S. Collins, Alexander W. Wiseman -- World Bank group education strategy 2020 / Christopher S. Collins, Alexander W. Wiseman -- Six questions about the World Bank's 2020 education sector strategy / M. Najeeb Shafiq -- When models become monopolies : the making of education policy at the World Bank / Stephen P. Heyneman -- The World Bank's "education strategy 2020" : a personal account / Robert F. Arnove -- Education sector strategy 2020 and popular participation : parallels and pitfalls / Tammy Boyd, Tom Owens -- The World Bank, the international finance corporation, and private sector participation in basic education : examining the education sector strategy 2020 / Karen Mundy, Francine Menashy -- Theory and ideology in the gender proposals of the World Bank's education strategy 2020 / Nelly P. Stromquist -- World Bank and education : ideological premises and ideological conclusions / Steven J. Klees -- Education and inequality : implications of the World Bank's education strategy 2020 / Devin Joshi, William Smith -- Constructing and measuring teacher effectiveness in global education reform / Rachael Gabriel, Richard Allington -- Deliberative educational planning : including educators' deliberations in educational policy making / Athena Vongalis-Macrow -- The approach of the World Bank to participation in development and education governance : trajectories, frameworks, results / D. Brent Edwards -- ICT, the education sector, and open e-learning : a unique opportunity for the decade ahead / Owen G. McGrath -- What doesn't the education sector strategy say? : how the fast track initiative and multisector operations are changing the landscape of World Bank education financing / Sarah Beardmore, John Middleton -- Taming the youth bulge in Africa : rethinking the World Bank's policy on technical and vocational education for disadvantaged youth in the knowledge economy / Chijioke J. Evoh -- Framing the World Bank education strategy 2020 to the Indian context : alignments, challenges, and opportunities / Supriya Baily -- The World Bank and educational reform in Indonesia / Victor J. Sensenig -- Increasing the flow of students, washing out quality : World Bank policy effects in Tanzanian secondary schools / Donna C. Tonini.
Includes indexes.
Print version record
Keywords: World Bank; Education -- Organizations & Institutions; Education -- Aims & Objectives; Educational strategies & policy; International institutions; Education and state; Education; Educational planning